Impact of Electronic Word of Mouth, Influencers, on Consumer Purchase Intentions on Fashion (Erigo Brand Study) - Aolia Ihsan Romadona; Maulana Harbi; Lis Tatin Hernidatiatin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the influence of electronic word of mouth (eWOM) and social media influencers on consumer buying intent, with an emphasis on the Indonesian fashion brand Erigo. The study aims to analyse how eWOM and influencers directly influence consumers’ purchase intention towards Erigo products. Data for this study were gathered using a quantitative methodology. through an online questionnaire from 150 active Users of social media between the ages of 18 and 40 in Cirebon City who are familiar with the Erigo brand. The sampling method followed Roscoe’s Rule of Thumb, while the data was examined using multiple regression analysis. Results indicate that although eWOM contributes to brand perception, It has no discernible impact on the intention to buy. On the other hand, influencers show a strong positive impact on consumer purchase intentions, with their digital presence and credibility contributing significantly to consumer interest. The study found that eWOM and influencers together explained 33.0% of the difference in consumers' purchase intentions, and the remaining 67.0% was due to other factors. The findings contribute to digital marketing theory by highlighting the dominant role of influencers over eWOM in shaping consumer behaviour.